Life cycle of a Kangaroo - Mukherjee, Vijita (New Delhi The Energy Resource Institute, 2011)
The penguin is one curious bird. It has strange wings, called flippers, but it cannot fly. And though penguins are awesome underwater swimmers, their chicks cannot swim. In fact, they don$1 (Bt even enter water till they grow up. Then, how do these chicks grow into diving champs who spend long hours in freezing seas? This book not only explains the amazing life cycle of a penguin, it also contains many interesting facts about this wonderful creature.s
Keywords: Kangaroo